Dietary intake of micronized avian eggshell membrane in aged mice reduces circulating inflammatory markers, increases microbiota diversity, and attenuates skeletal muscle aging - Rønning, Sissel Beate; Carlsen, Harald; Rocha, Sérgio Domingos Cardoso; Rud, Ida; Solberg, Nina; Høst, Vibeke; Veiseth-Kent, Eva; Arnesen, Henriette; Bergum, Silje; Kirkhus, Bente; Böcker, Ulrike; Abedali, Nada; et al. (Frontiers in Nutrition, 2024)
Avian eggshell membrane (ESM) is a complex extracellular matrix comprising collagens, glycoproteins, proteoglycans, and hyaluronic acid. We have previously demonstrated that ESM possesses anti-inflammatory properties in vitro and regulates wound healing processes in vivo.The present study aimed to investigate if oral intake of micronized ESM could attenuate skeletal muscle aging associated with beneficial alterations in gut microbiota profile and reduced inflammation. Elderly male C57BL/6 mice were fed an AIN93G diet supplemented with 0, 0.1, 1, or 8% ESM. Young mice were used as reference. The digestibility of ESM was investigated using the static in vitro digestion model INFOGEST for older people and adults, and the gut microbiota profile was analyzed in mice. In addition, we performed a small-scale pre-clinical human study with healthy home-dwelling elderly (> 70 years) who received capsules with a placebo or 500 mg ESM every day for four weeks and studied the effect on circulating inflammatory markers. Intake of ESM in elderly mice impacted and attenuated several wellknown hallmarks of aging, such as a reduction in the number of skeletal muscle fibers, the appearance of centronucleated fibers, a decrease in type IIa/IIx fiber type proportion, reduced gene expression of satellite cell markers Sdc3 and Pax7 and increased gene expression of the muscle atrophy marker Fbxo32. Similarly, a transition towards the phenotypic characteristics of young mice was observed for several proteins involved in cellular processes and metabolism.The digestibility of ESM was poor, especially for the elderly condition. Furthermore, our experiments showed that mice fed with 8% ESM had increased gut microbiota diversity and altered microbiota composition compared with the other groups. ESM in the diet also lowered the expression of the inflammation marker TNFA in mice and in vitro in THP-1 macrophages.In the human study, intake of ESM capsules significantly reduced the inflammatory marker CRP. Altogether, our results suggest that ESM, a natural extracellular biomaterial, may be attractive as a nutraceutical candidate with a possible effect on skeletal muscle aging possibly through its immunomodulating effect or gut microbiota.